Serum Liver Proteins and 17 β -estradiol in Postmenopausal Women with Breast Cancer - Zahra Tahmasebi Fard; Fatemeh Rouhollah; Nahid Nafisi (Research in Molecular Medicine, 2018)
Background: Breast cancer is a hormone-dependent malignancy that is associated with estrogen and progesterone interactions. The liver is the most important organ to be affected by the metastasis of breast cancer, which causes functional impairment.We compared levels of obesity, 17β-estradiol, and secreted proteins in postmenopausal women with breast cancer but without hepatic symptoms to those in healthy postmenopausal women.Materials and Methods: We recruited 105 postmenopausal women with breast cancer but without any clinical hepatic symptoms based on a physician's diagnosis, and 105 healthy postmenopausal women. After taking blood samples, we separated the serum and determined the levels of alanine aminotransferase (ALT), enzyme aspartate aminotransferase (AST), sex hormone-binding globulin (SHBG), and 17β-estradiol using an enzyme-linked immunosorbent assay (ELISA). The results were statistically analyzed using SPSS.Results: The mean ages of the subjects in the cancer and control groups were 60.88 ± 0.85 and 55.56 ± 0.81 years, respectively. The exception ages (p=0.002), body mass index (BMI) values (p=0.033), serum glutamic oxaloacetic transaminase (SGOT) levels/AST levels (p=3.1*10 - 4 ), serum glutamic pyruvic transaminase (SGPT) levels/ALT levels(p=0.001), SHBG levels(p=0.014), and 17β-estradiol levels(p=0.003) in the serum differed significantly between the groups. Moreover, the mean serum 17β-estradiol (E2) levels and weights were higher in the cancer group than in the control group. Nevertheless, the mean serum levels of synthetic liver enzymes (SHBG, ALT, and AST) were lower in the cancer group than in the control group.Conclusion: In general, the postmenopausal cancer patients had higher serum estrogen levels and BMIs than their healthy counterparts. Furthermore, the levels of liver enzymes apparently decreased in the cancer group, probably owing to liver malfunction.